Research on performance of vehicle semi-active suspension applied magnetorheological damper based on linear quadratic Gaussian control. (July 2020) - Sha, Shujing; Wang, Zhongnan; Du, Haiping
With the development of automobile technology, the traditional passive suspension cannot meet people's requirements for vehicle comfort and safety. For this reason, a variable damping semi-active suspension applied magnetorheological damper is proposed. By collecting various performance parameters of the front suspension, the optimal feedback control matrix is obtained by applying linear quadratic Gaussian control strategy, and the optimal damping force output is also obtained to improve comfort and vehicle safety by reducing vibration. The semi-active suspension model of a quarter vehicles was established by MATLAB/Simulink, and the simulation experiment was carried out. The results show that the semi-active suspension system with magnetorheological damper is superior to the traditional passive suspension in terms of vibration absorption; meanwhile, the root mean square values of vehicle acceleration, suspension dynamic deflection, tire dynamic travel, and tire dynamic load are reduced, which effectively improve the vehicle ride stability.